2019
DOI: 10.1002/ece3.4785
|View full text |Cite
|
Sign up to set email alerts
|

Body mass as a supertrait linked to abundance and behavioral dominance in hummingbirds: A phylogenetic approach

Abstract: Body mass has been considered one of the most critical organismal traits, and its role in many ecological processes has been widely studied. In hummingbirds, body mass has been linked to ecological features such as foraging performance, metabolic rates, and cost of flying, among others. We used an evolutionary approach to test whether body mass is a good predictor of two of the main ecological features of hummingbirds: their abundances and behavioral dominance. To determine whether a species was abundant and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 82 publications
0
13
0
4
Order By: Relevance
“…Here, body mass holds some promise; labelled a 'supertrait' (Bribiesca et al 2019) due to its role in numerous ecological processes, wide availability, and universality, it provides a convenient tool enabling direct comparison between taxa. Further linked with an increased vulnerability to strong population decline (Deinet et al 2020) and extinction, body mass has also been suggested as a potential predeterminant of stressor exposure (Collen et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Here, body mass holds some promise; labelled a 'supertrait' (Bribiesca et al 2019) due to its role in numerous ecological processes, wide availability, and universality, it provides a convenient tool enabling direct comparison between taxa. Further linked with an increased vulnerability to strong population decline (Deinet et al 2020) and extinction, body mass has also been suggested as a potential predeterminant of stressor exposure (Collen et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, body size has been portrayed as one of the most direct links between microevolution and macroevolution (Maurer et al 1992; Jablonski 1996). Indeed, almost inevitably, different body sizes will carry competitive advantages in different ecological circumstances (Brown and Maurer 1986; Woodward et al 2005; White et al 2007; Bribiesca et al 2019). A widely debated but still open question is whether any particular body sizes carry universal competitive advantages across all possible ecologies.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, resource partitioning among hummingbirds has been explained by different mechanisms related to differences in the use of nectar (Justino, Maruyama, & Oliveira, 2012;Lyon, 1976), which include variation in foraging behavior (Feinsinger & Colwell, 1978;Lara, Lumbreras, & González, 2009;Sandlin, 2000;Stiles, 1985), population movements at the landscape scale following the phenology of their plants (Buzato, Sazima, & Sazima, 2000;Des Granges, 1979;Ortiz-Pulido & Vargas-Licona, 2008), microhabitat differences (Kodric- Brown, Brown, Byers, & Gori, 1984;Ritchie, 2002), spatiotemporal segregation in resource use (Lara, 2006;Lara et al, 2011;Ornelas et al, 2002), and phylogenetic distance between species (Márquez-Luna et al, 2018;Martin & Ghalambor, 2014). Likewise, it has been proposed that interspecific morphological variations in traits, such as body size and bill length and curvature, play an important role in this resource partitioning (Bribiesca, Herrera-Alsina, Ruiz-Sánchez, Sánchez-González, & Schondube, 2019;López-Segoviano, Bribiesca, & Arizmend, 2018;Lyon, 1976;Maglianesi, Bohning-Gaese, & Schleuning, 2015;Rodríguez-Flores & Stiles, 2005;Snow & Snow, 1980;Stiles, 1975). Thus, several of these coexistence mechanisms are based on the behavioral, morphological, and physiological capability of hummingbirds to exploit such a heterogeneous spatio-temporal resource as nectar (Bacon, Hurly, & Healy, 2011;Ritchie, 2002).…”
mentioning
confidence: 99%